Evaluating RNR-Based Targeted Treatment and Intervention Dosage in the Context of Traumatic Exposure - Baglivio, Michael T. (Youth violence and juvenile justice, 2021)
Best practices in juvenile justice call for the individualized matching of services to assessed dynamic risk factors, with services delivered at sufficient dosage. However, prior work has largely ignored whether this recipe for recidivism reduction is as effective for adolescents with extensive traumatic exposure as it is for those without. The current study leverages a statewide sample of 1,666 juveniles released from residential placement (84.6% male, 59.8% Black, 11.9% Hispanic). We examine the associations of individual-level service matching and achieving dosage targets established by Lipsey’s Standardized Program Evaluation Protocol (SPEP) during residential placement with changes in dynamic risk during placement and recidivism post-release among juveniles with extensive adverse childhood experiences (ACE) exposure and those without. Results demonstrate heightened traumatic exposure is related to smaller reductions in dynamic risk and to an increased probability of reoffending, but that youth receiving matched services coupled with adequate dosage leads to greater treatment progress (dynamic risk reduction) and lower recidivism post-release for both low-ACE and high-ACE youth. Implications for juvenile justice practice and policy are discussed.